Analisis Legal Standing dan Konsistensi Putusan Mahkamah Konstitusi dalam Pengujian Materiil UU Nomor 7 Tahun 2017 tentang Pemilihan Umum: Studi Kasus Putusan No.90/PUU-XXI/2023 - Amran Anshary Kelilauw; Zuhad Aji Firmantoro (Dinasti Review Publisher, 2024)
This research reviews constitutional review at the Constitutional Court (MK), especially in Case No.90/PUU-XXI/2023. The focus is on the applicant's legal standing and the Constitutional Court's considerations in making decisions. Legal standing is a legal right or position that allows a party to file a lawsuit before a court. In the context of material review, the applicant's legal position is the main determinant of the legitimacy of judicial review. Normative legal methods are used in this research to systematically and in-depth analyze the legal framework governing legal standing and the Constitutional Court's interpretation of it in the context of the cases studied. This research discusses the requirements and criteria for legal standing which are regulated in both the law and MK regulations, as well as the MK's interpretation of them in this case. The results show a debate surrounding the consistency, independence, and integrity of the Constitutional Court, especially regarding the controversial decisions received. Criticism emerged regarding the Constitutional Court's approach in assessing legal standing, where there were allegations of inconsistencies, loose assessments, and potentially dubious conflicts of interest. Thus, this research provides in-depth insight into the constitutional review process and the challenges faced by the Constitutional Court in maintaining its authority as an independent and credible constitutional justice institution.